Using 0/1 mixed integer linear programming to solve a reliability-centered problem of power plant preventive maintenance scheduling - Perez Canto, Salvador (Optimization and engineering, 2011)
The problem of power plant preventive maintenance scheduling is studied in this paper. A reliability perspective is considered. This problem consists of ascertaining which generating units must halt production to be examined regularly for safety. It is very important because a failure in a power station may cause a general breakdown in an electric network. The main consequence is that the electricity demand of customers will not be satisfied in such cases. Therefore, reliability is the key point used in the methodology presented. The problem is approached under the operations research perspective as an optimization issue. 0/1 mixed integer linear programming is used to solve the model reached. An application study is included. The model is put to use in a real power plant setting, representative of the Spanish one. The result obtained is a schedule that allows the efficient organization of preventive maintenance over a specific time horizon.